Blue ocean strategy : how to create uncontested market space and make the competition irrelevant - Kim, W. Chan; Mauborgne, Renée (Boston, Massachusetts : Harvard Business Review Press, 2015)
"Presents a systematic approach to making the competition irrelevant and outlines principles and tools any organization can use to create and capture their own blue oceans."Book jacket
Creating blue oceans -- Analytical tools and frameworks -- Reconstruct market boundaries -- Focus on the big picture, not the numbers -- Reach beyond existing demand -- Get the strategic sequence right -- Overcome key organizational hurdles -- Build execution into strategy -- Align value, profit, and people propositions -- Renew blue oceans -- Avoid red ocean traps.
"With a new preface, fresh chapters, and updated case studies"--Back of jacket.
Includes bibliographical references (pages 263-270) and index.
Print version record.
Keywords: New products; Market segmentation; Market segmentation; New products; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books